PENDAMPINGAN BUDIDAYA CACING SUTRA HIGIENIS DAN BERKELANJUTAN DI KOTA AGUNG - LAMPUNG - Umidayati Umidayati; Sinung Rahardjo; Moch Nurhudah; Meuthia Aulia Jabbar; Luchiadini Ika Pamarhayani; Khaerudin Khaerudin; Ita Junita Puspita Dewi; Artin Indrayati; Juarsa Juarsa; Agus herikuswoyo (Jurnal Abdi Insani, 2023)
Introduction To meet the natural food for fish cultivators, community assistance was held in the village of Way Gelang, Tanggamus, Lampung. about hygienic and sustainable cultivation of silk worms. Increasing income to become a fisherman whose income is uncertain. This village has formed a business group for growing tilapia and catfish cultivation under the auspices of SUPM Kotaagung, to meet the needs for catfish and tilapia seeds they still buy from outside at quite high prices. As well as the high price, with training to the community about hygienic and sustainable silk worm cultivation, it is hoped that the community can cultivate silk worms for fish hatchery for their own consumption and can be sold to hatchery farmers so they can reduce operational costs and get additional income from the sale of silk worms. Objective of the activity: to assist fish farmers in cultivating silkworms hygienically and sustainably. Methods of activities for establishing cultivation groups, outreach, training, mentoring from pre-production to production. The results of community activities are able to cultivate silkworms well. The conclusion of the mentoring activities was very well received by the hatchery farming community in Way Gelang Lampung Village by providing direct techniques on silkworm cultivation.